TRANSLATING MATHEMATIC TEXT ABILITY OF FIFTH SEMESTER STUDENTS IN MATH AND SCIENCE DEPARTMENT STKIP YPM BANGKO - Hera hartati (INOVISH JOURNAL, 2020)
The aimed of this research is to describe about students’ ability  in translating mathematic  text as a material in English for Teaching Math Course at fifth semester in Math Education Program,  Math and Sciece Department of STKIP YPM Bangko in academic year 2019/2020. This ability to provide students to be bilingual teacher in math subject. This reasearch is descriptive quantitave research. It will be conducted in Math Education Program of STKIP YPM Bangko. The population is fifth semester students consists of 18 students. It uses total sampling, the researcher will use written test as the instruments of collecting data, it consists about translating mathematics operation, translating mathematic problem, and passage about mathematics. The students are asked to translate from target language to sourse language and source language to target language. In analyzing the data, the researcher will use the procedure reduce the data, classify the data, describe the data, and data display. To know about students’ ability in translating mathematics english text, the researcher will use three indicatorss; accuracy, readability and acceptability. It also categories into 4 level mastery; excellent, good, fair, and poor. The result of this research found that Students’ ability in translating mathematic text was excellent. Based on the aspect of mathematic text, mathematic passage was difficult to translate for them, and accuracy indicator was lowest score, they tend to omitted word and change the spelling. It can be suggested to train students to practice more the interaction to the text and use the effective strategy in translation.